Research into partial problems in building brand image in selected small and medium-sized enterprises of chemical industry in the Czech Republic - Jelínková, Martina; Munzarová, Simona (Univerzita Hradec Králové, 2020)
While the importance of brands in the current B2C and B2B markets continues to grow, the issue of brand management and brand image building in small and medium-sized enterprises has not been consistently mapped. These types of businesses are faced with specific problems in their efforts to promote their brands, which need to be better understood and analysed. The primary qualitative research was carried out in the form of in-depth structured interviews with managers of three lines of business dealing with the processing and production of chemical products within three different Czech companies. The aim of the research was to analyse the current situation in selected companies in terms of creating and using brands, perception of the value and importance of brands as well as ways of creating the desired brand positioning and image. The research has made it possible to identify several general problem areas in brand management, the solution of which would probably make it possible to improve the brand image, both in the enterprises under review and in similar small and medium-sized enterprises.
Výzkum dílčích problémů při budování image značek ve vybraných malých a středních podnicích chemického průmyslu v ČR
Keywords: branding; brand image; chemical industry; small and medium-sized enterprises (SMEs); branding; image značek; chemický průmysl; malé a střední podniky